1988
DOI: 10.1016/0166-445x(88)90052-5
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative structure-activity relationship for the acute toxicity of some epoxy compounds to the guppy

Abstract: The 14 day LCso values of various epoxy compounds to the guppy (Poecilia reticulata) were determined, and investigated through the construction of a quantitative structure-activity relationship (QSAR). Both hydrophobicity and alkylating potency of the compounds are found to be necessary parameters for the satisfactory description of the LCs0 data. The findings of the present study are compared to results published for halogenated alkylating agents (Hermens, 1985), some of which are considerably more toxic than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 19 publications
4
55
3
Order By: Relevance
“…It has been shown that the aquatic toxicity of several different classes of electrophilic organic compounds can very well be modeled with a two-parameter QSAR equation using the compounds' log K ow and its reaction rate constant toward NBP (log k NBP ) as parameters. Very good examples of these kinds of models can be found in Hermens et al [14] and Deneer et al [17,18]. Their results are clearly in accordance with the idea that for a major part of organic chemicals, the aquatic toxicity can be regarded as a sum of baseline toxicity modeled by log K ow and an excess toxicity.…”
Section: Qsars and Chemical Reactivitysupporting
confidence: 57%
See 1 more Smart Citation
“…It has been shown that the aquatic toxicity of several different classes of electrophilic organic compounds can very well be modeled with a two-parameter QSAR equation using the compounds' log K ow and its reaction rate constant toward NBP (log k NBP ) as parameters. Very good examples of these kinds of models can be found in Hermens et al [14] and Deneer et al [17,18]. Their results are clearly in accordance with the idea that for a major part of organic chemicals, the aquatic toxicity can be regarded as a sum of baseline toxicity modeled by log K ow and an excess toxicity.…”
Section: Qsars and Chemical Reactivitysupporting
confidence: 57%
“…To those ends we describe the calculation of ⌬S ‡ and ⌬H ‡ for a training set of small organic electrophiles (a set of compounds that readily reacts or is expected to react with 4-nitrobenzylpyridine) and the subsequent modeling of the experimentally determined log k NBP from these calculated parameters. Furthermore, we compare the modeling of the acute aquatic toxicity LC50 using both the experimentally determined log k NBP , as described by Hermens et al [14] and Deneer [17,18], and the calculated reactivity. It should be noted that the MOPAC-optimized geometries of the compounds and reaction transition states under investigation refer to isolated molecules in vacuo, whereas the experimentally determined log k NBP is measured in a boiling solution of, for example, 2-butanone.…”
Section: Modeling Reactivity Mechanisticallymentioning
confidence: 99%
“…The chloride ions in salt water accelerate the chemical degradation to a half-life of 4.1 d [126]. PO is practically nontoxic to fish on a static acute basis (LC 50 >100 mg/L) [129][130][131][132][133]. Biodegradation of PO under aerobic static laboratory conditions is high (BOD 20 PO evaporates relatively rapidly from dry soil surfaces, and it is moderately volatile from water and wet soils, but the evaporation rate is diminished by leaching.…”
Section: Chemical Oxygen Demand (Cod)mentioning
confidence: 99%
“…Similar to the ASTER system, the EU uses QSARs to estimate toxicity for nonreactive substances. The recommended QSARs are summarized in Table 3 and are based on empirical data sets developed at the University of Utrecht, The Netherlands, and the U.S. EPA [57,60,[71][72][73][74][75][76][77][78]. These data sets were reanalyzed for the EU ranking effort [79].…”
Section: Use Of Qsars To Characterize Effects In Aquatic Organismsmentioning
confidence: 99%